1999
DOI: 10.1177/014556139907801211
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Laser Stapedotomy with and without Preservation of the Stapedius Tendon

Abstract: Our go al was to investigate the postope rative diffe ren ces in hearing between patients who had had their stape dius tendon sa cr ificed and tho se whose stap edius tendon was preserv ed du ring las er stapes surgeryfo rotosclerosis. To that end, we perfonn ed a retrospecti ve review by ma iling exte nsive qu estionnaires to patients who had been operat ed on bet ween 1994 and 1997. We also perform ed routine and special audiom etr ic testin g to au gm eilt the subjective data. Seventy-nine of 124 questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The stapedial reflex, speech discrimination in loud noise, noise tolerance level, and the patients' subjective outcomes questionnaires are being evaluated currently to defermine whether additional evidence justifying preservation of the stapedius tendon can be obtained. These results will be presented in the near future 16 …”
Section: Discussionmentioning
confidence: 83%
“…The stapedial reflex, speech discrimination in loud noise, noise tolerance level, and the patients' subjective outcomes questionnaires are being evaluated currently to defermine whether additional evidence justifying preservation of the stapedius tendon can be obtained. These results will be presented in the near future 16 …”
Section: Discussionmentioning
confidence: 83%
“…In fact, it has been widely debated about a possible ST preservation during this procedure to prevent the devascularization and necrosis of the LPI. Although many authors have reported excellent objective and subjective results in patients who underwent to stapedectomy or stapedotomy with ST preservation, its usefulness is still controversial [13][14][15][16][17][18][19]. In addition, according to our findings, the BFD of the stapedial vessels seems to have an opposite direction to the LPI.…”
Section: Discussionmentioning
confidence: 43%
“…Moreover, application of the prosthesis was easier with stiff and intact ossicular chain (Silverstein et al). 23…”
Section: Discussionmentioning
confidence: 99%